Essential Thrombocytosis in a Postmenopausal Female a Rare Cause of Aquagenic Pruritus - Prabhat Agrawal; Ruchika Garg; Shiv Sagar Yadav; Sandipta Panda (Wolters Kluwer Medknow Publications, 2024)
Essential thrombocytosis (ET) is a hematopoietic stem cell disorder in which the overproduction of platelets without a definable cause occurs. Its incidence is 1-2 per 100,000 population with female preponderance. These myeloproliferative disorders are associated with many dermatological manifestations such as pruritus and erythromelalgia. Here, we are reporting the case of a 61-year-old female with ET with aquagenic pruritus (AP), although AP is associated more with polycythemia vera.